2013
DOI: 10.1161/circulationaha.112.001233
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Dabigatran Plasma Levels and Their Relation to Bleeding

Abstract: Background-Fixed-dose unmonitored treatment with dabigatran etexilate is effective and has a favorable safety profile in the prevention of stroke in atrial fibrillation patients compared with warfarin. We hypothesized that genetic variants could contribute to interindividual variability in blood concentrations of the active metabolite of dabigatran etexilate and influence the safety and efficacy of dabigatran. Methods and Results-We successfully conducted a genome-wide association study in 2944 Randomized Eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
204
4
23

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(240 citation statements)
references
References 30 publications
(27 reference statements)
9
204
4
23
Order By: Relevance
“…Dabigatran is a potent competitive thrombin inhibitor [2], inhibiting both fibrin-bound and unbound thrombin. Dabigatran has a low oral bioavailability, ranging from 3 to 7 % and is predominantly cleared (80 %) by the kidneys [1,2,29,35]. The recommended dosage for prevention of stroke in patients with nonvalvular AF and for treatment and secondary prevention of venous thromboembolism is 150 mg twice daily [1].…”
Section: Pharmacologic Basis For Extracorporeal Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Dabigatran is a potent competitive thrombin inhibitor [2], inhibiting both fibrin-bound and unbound thrombin. Dabigatran has a low oral bioavailability, ranging from 3 to 7 % and is predominantly cleared (80 %) by the kidneys [1,2,29,35]. The recommended dosage for prevention of stroke in patients with nonvalvular AF and for treatment and secondary prevention of venous thromboembolism is 150 mg twice daily [1].…”
Section: Pharmacologic Basis For Extracorporeal Removalmentioning
confidence: 99%
“…For example, a recent analysis demonstrated that the single-nucleotide polymorphism of carboxylesterase-1, rs2244613, was present in 32.8 % of subjects enrolled in the RE-LY trial, which was found to be protective as lower trough concentrations of dabigatran and correlate with a lower risk of bleeding [35]. In addition, polymorphisms in ABCB1, the gene that encodes P-glycoprotein, can influence the bioavailability of dabigatran [23,44].…”
Section: Pharmacologic Basis For Extracorporeal Removalmentioning
confidence: 99%
“…Despite the claim that dabigatran treatment does not to require laboratory-guided dose adjustment, due to the low bioavailability ( < 6.5%), predominant renal elimination ( > 80%) [7], and genetic variants' influence on the responses to dabigatran [9], assessing the intensity of anticoagulation may be useful in patients at risk of overdose and in highrisk (both for thromboembolism and for bleeding) patients in general [10]. The standard for measuring NOAC concentrations in biological fluids is high-performance liquid chromatography coupled with tandem mass spectrometry (HPLC-MS/MS).…”
Section: Introductionmentioning
confidence: 99%
“…However, important pharmacologic differences exist among the drugs in this class. Most commonly prescribed ACE inhibitors (including ramipril, trandolapril, enalapril and perindopril) are prodrugs that are de‐esterified to active metabolites (ramiprilat, trandolaprilat, emalaprilat and perindoprilat, respectively) by the enzyme carboxylesterase 1 (CES1), an enzyme highly expressed in liver and increasingly appreciated as an important factor in drug metabolism 9, 10, 11, 12. In contrast, lisinopril and captopril are active ACE inhibitors that require no such bio‐activation 13.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, lisinopril and captopril are active ACE inhibitors that require no such bio‐activation 13. Genetic variation in CES1 has been shown to influence drug metabolism and may influence the antihypertensive effects of ACE inhibitors such as imidapril 11, 14, 15, 16, 17, 18.…”
Section: Introductionmentioning
confidence: 99%